Optimizing Local Government Strategies for Developing a Creative Economy in Coastal Tourism Areas - Slamat, Ali; Matitaputty, Izaac Tonny; Ramly, Fahrudin (Public Policy, 2025)
Tourism significantly contributes to Indonesia’s economic growth, with the creative economy enhancing destination competitiveness. This study examines the integration of the creative economy in developing coastal tourism at Tanjung Tatulain, Negeri Hitu Messing, Central Maluku. Using qualitative methods, data were collected through interviews, questionnaires, and observations, analyzed via SWOT and stakeholder synergy models. Findings highlight strong tourism potential but identify challenges such as infrastructure gaps, weak promotion, and land issues. Addressing these requires government support, stakeholder collaboration, and community involvement. Strategic improvements in infrastructure, marketing, and sustainability are essential for maximizing tourism’s economic and social benefits.